Dampak Sosial Ekonomi Pembangunan Pembangkit Listrik Tenaga Surya (PLTS) Sumbawa 26 MWp Terhadap Masyarakat - Suprianto Naim (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2022)
One of the energies strongly needed by humans is electrical energy. Currently, Solar Power Plant (henceforth, PLTS) is a source of renewable electrical energy and widely developed since PLTS is environmentally friendly and easy to obtain, specifically for the countries are on the equator such as Indonesia. One of the PLTS with a large capacity developed by PT. Amman Mineral Nusa Tenggara (PT. AMNT) in collaboration with PT. Medcopower Solar Sumbawa (PT. MPSS) and PT. Sinergi Era Cemerlang (PT. SEC) as the executor. The PLTS, with 26 MWpcapacity, built in the Tongo Village area, Sekongkang District, West Sumbawa Regency, NTB. This PLTS is known as PLTS Sumbawa 26 MWp. The existence of this project definitely has a socio-economic impacts on the community, either positive or negative impacts. The qualitative data analysis results show the socio-economic effects of the PLTS Sumbawa 26 MWp development, namely increasing labor absorption; increasing Village Original Income (PADes) such as waste retribution; improvement of village infrastructure, especially places of worship, educational facilities, garbage disposal sites, and assistance for social activities; and changes in public perception in the form of social jealousy.